Pharmacological Approach to Glycemic Treatment Using Black, Green and Herbal Tea Extracts (Bangladesh Journal of Botany, 2021)
Tea is the second most widely used drink all over the world after water. It has several health benefits. The aqueous and methanolic extracts of black, green and herbal teas for the treatment of hyperglycemia and its associated complications were investigated. Nine tea samples including black, green and herbal teas namely Lipton black tea (LBT), Supreme black tea (SBT), Tapal black tea (TBT), Jasmine green tea (JGT), Lemon grass green tea (LGrT), Lemon green tea (LGT), Berginia ciliata, Bistorta affinis and Paeonia emodi were selected for the study. Total phenolic contents (TPC), total flavonoid contents (TFC), antioxidant properties including inhibitory activity against 2,2'-azino-bis (3-ethylbenzothiazoline-6-sulphonic acid) radical (ABTS•+), iron chelation and enzymes inhibitory potential for alpha glucosidase and alpha amylase were analyzed based on in vitro assays. The percentage yield of extracts was in the range of 7.2 to 47 %. Methanolic extracts showed greater TPC values (μg GAE/g) while aqueous extracts showed greater TFC values (μg Rutin E/g). The aqueous extracts of most of the studied tea samples showed strong biological activities with very low IC50 (50% inhibitory concentration) values (0.2-69.0 μg/ml) for ABTS•+ radical scavenging, Fe2+ chelation and alpha glucosidase inhibition assays. For amylase inhibition activity, some aqueous extracts including LBT, SBT, JGT and P. emodi exhibited greater IC50 values.Bangladesh J. Bot. 50(3): 491-498, 2021 (September)